Defining stopping criteria for ending randomized clinical trials that investigate the interruption of transmission of soil-transmitted helminths employing mass drug administration - Werkman, Marleen; Toor, Jaspreet; Vegvari, Carolin; Wright, James E.; Truscott, James E.; Ásbjörnsdóttir, Kristjana H.; Rubin Means, Arianna; Walson, Judd L.; Anderson, Roy M. (PLOS Neglected Tropical Diseases, 2018)
Author summary Soil-transmitted helminths (STH) remain prevalent in many African, South American and Asian countries. The WHO recommends treating pre-school aged children (pre-SAC) and school-aged children (SAC) in areas with endemic STH infections. However, treating pre-SAC and SAC only is unlikely to achieve STH transmission interruption, as adults remain infected and contribute to re-infection in the community, particularly with hookworm. Treating the entire community with high-coverage and high-frequency mass drug administration (MDA) may achieve transmission interruption and ongoing community-based clinical trials are investigating the feasibility and impact of such an approach. Since large-scale trials are costly and STH prevalence may bounce back quickly to pre-treatment levels when MDA ceases, it may be more efficient to stop the trial when interruption of transmission can be ruled out. In these circumstances it may be necessary to investigate why transmission interruption was not achieved to inform necessary improvements in future community-wide treatment programmes. Factors that may affect the likelihood of transmission interruption include water, sanitation and hygiene (WASH), sociodemographic, migration and environmental factors. These factors should be investigated in cases where interruption of transmission is not achieved. In this study, we investigate the stopping criteria required to determine whether transmission interruption has occurred following multiple rounds of MDA.